Occurrence of Allergic Contact Dermatitis in Rajshahi City and its relation with some of the socio-demographic characteristics - Hossain, ZMM; Mansur, MH Ali (TAJ: Journal of Teachers Association, 2018)
There is no detailed and updated data on Allergic Contact Dermatitis (ACD) in our country. The present study is designed in thissituation to reveal the occurrence of allergic contact dermatitis in Rajshahi city and its association with some of the socio-demographic characteristics like sex, socio-economic status, co-morbidity etc.It was a cross-sectional type of descriptive study, conducted upon the general population of urban community of Rajshahi City. 153 respondents were randomly selected of which 76 were male and the rest 77 were female. People of all the ages and all the family members of the selected areas were included in the study, who were present at home at the time of data collection. Data were collected by face-to-face interview with the help of a semi-structured questionnaire. Allergic contact dermatitis was clinically diagnosed by the researchers themselves by direct physical examination after obtaining their symptoms, with the help of common medical equipments like a magnifying glass, a torch etc. Verbal consents were taken for ethical consideration. Occurrence of allergic contact dermatitis was found to be 20.26% in the urban community of Rajshahi City of which 18.42% were male and 22.08% were female – statistically no significant difference was there. Among the different socio-economic status, the middle class had the highest occurrence rate (28.41%) and Chi-square test showed here statistically significant difference between the groups [X2 = 10.591, df=2, p=0.00501411]. The co-morbidity was found to be higher in female respondents with a statistically significant difference [X2 = 5.231 , df = 1, p = 0.02218777]. TAJ 2016; 29(2): 42-46